Arylsulfatase K inactivation causes mucopolysaccharidosis due to deficient glucuronate desulfation of heparan and chondroitin sulfate. Issue 17 (17th September 2020) - Trabszo, Christof; Ramms, Bastian; Chopra, Pradeep; Lüllmann-Rauch, Renate; Stroobants, Stijn; Sproß, Jens; Jeschke, Anke; Schinke, Thorsten; Boons, Geert-Jan; Esko, Jeffrey D.; Lübke, Torben; Dierks, Thomas
Abstract : Mucopolysaccharidoses comprise a group of rare metabolic diseases, in which the lysosomal degradation of glycosaminoglycans (GAGs) is impaired due to genetically inherited defects of lysosomal enzymes involved in GAG catabolism. The resulting intralysosomal accumulation of GAG-derived metabolites consequently manifests in neurological symptoms and also peripheral abnormalities in various tissues like liver, kidney, spleen and bone. As each GAG consists of differently sulfated disaccharide units, it needs a specific, but also partly overlapping set of lysosomal enzymes to accomplish their complete degradation. Recently, we identified and characterized the lysosomal enzyme arylsulfatase K (Arsk) exhibiting glucuronate-2-sulfatase activity as needed for the degradation of heparan sulfate (HS), chondroitin sulfate (CS) and dermatan sulfate (DS). In the present study, we investigated the physiological relevance of Arsk by means of a constitutive Arsk knockout mouse model. A complete lack of glucuronate desulfation was demonstrated by a specific enzyme activity assay. Arsk-deficient mice show, in an organ-specific manner, a moderate accumulation of HS and CS metabolites characterized by 2- O -sulfated glucuronate moieties at their non-reducing ends. Pathophysiological studies reflect a rather mild phenotype including behavioral changes. Interestingly, no prominent lysosomal storage pathology like bone abnormalities were detected. Our results from the Arsk mouse model suggest a new although mild form of mucopolysacharidose (MPS), which we designate MPS type IIB.